1999
DOI: 10.1207/s15327558ijbm0601_2
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a pilot program to promote exercise among mothers of preschool children

Abstract: The health benefits of physical activity are well documented, but mothers of young children experience significant barriers to exercise. A 10-week minimal-intervention exercise program, involving a weekly meeting at which child care was provided, and guidance in establishing independent exercise was developed on the basis of previous research with this population group. Thirty-two women with children under age 5, and in the contemplation or preparation stages of exercise behavior change, were recruited from Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 34 publications
2
29
2
Order By: Relevance
“…As a group, working mothers exhibit high levels of inactivity, which can largely be attributed to the numerous real and perceived physical activity barriers they encounter (Brown et al, 2001;Burke et al, 2004;Cramp and Bray, 2011;Verhoef and Love, 1994). As declining levels of physical activity across the transition into motherhood have emerged as a legitimate public health concern, several interventions designed specifically for women with children have been developed (Cody and Lee, 1999;Cramp and Brawley, 2006;Fahrenwald et al, 2004;Fjeldsoe et al, 2010). Most recently, a brief, social cognitive theorybased intervention to increase physical activity among working mothers demonstrated positive effects on self-reported physical activity (Mailey and McAuley, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As a group, working mothers exhibit high levels of inactivity, which can largely be attributed to the numerous real and perceived physical activity barriers they encounter (Brown et al, 2001;Burke et al, 2004;Cramp and Bray, 2011;Verhoef and Love, 1994). As declining levels of physical activity across the transition into motherhood have emerged as a legitimate public health concern, several interventions designed specifically for women with children have been developed (Cody and Lee, 1999;Cramp and Brawley, 2006;Fahrenwald et al, 2004;Fjeldsoe et al, 2010). Most recently, a brief, social cognitive theorybased intervention to increase physical activity among working mothers demonstrated positive effects on self-reported physical activity (Mailey and McAuley, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A small number of such interventions have specifically targeted mothers, and the results thus far have been promising, with all studies reporting some positive changes in behavioral outcomes (Cody & Lee, 1999;Cramp & Brawley, 2006;Fahrenwald et al, 2004;Fjeldsoe et al, 2010).…”
mentioning
confidence: 99%
“…Maternal stress has been identified as a factor that might disrupt mothers' level of exercise involvement; however, it has not been systematically examined with respect to its effect on adopting PA (Cody & Lee, 1999). Mothers in the current study identified several stressors related to motherhood (e.g., their children not getting along with one another) that are similar to those reported in previous studies of primarily non-Hispanic white and non-Hispanic black mothers and have been associated with poor physical and emotional health outcomes (Stephens, Franks, & Townsend, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary evidence from these studies suggests that these interventions are potentially effective in increasing motivation to exercise, increasing daily energy expenditure, and mobilizing mothers towards meeting current guidelines for moderate-intensity PA (Fahrenwald et al, 2004;Miller et al, 2002). Although these studies demonstrate that mothers are in fact interested in programs that promote PA and can successfully adopt more physically active lifestyles, familyrelated constraints and maternal stressors continue to be factors that disrupt their level of exercise (Cody & Lee, 1999). Therefore, it is important to examine systematically which aspects of motherhood might influence successful adoption of moderate PA, particularly among low-income and ethnically diverse mothers, given that previous studies have focused on primarily non-Hispanic white populations (Miller et al, 2002;Verhoef & Love, 1994;Verhoef et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation